2018
DOI: 10.3390/hydrology5030033
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes of Precipitation IDF Curves for Short Duration under Climate Change in Central Vietnam

Abstract: Abstract:In future years, extreme weather events are expected to frequently increase due to climate change, especially in the combination of climate change and events of El Niño-Southern Oscillation. This pays special attention to the construction of intensity-duration-frequency (IDF) curves at a tempo-spatial scale of sub-daily and sub-grid under a context of climate change. The reason for this is that IDF curves represent essential means to study effects on the performance of drainage systems, damps, dikes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
6
1
3
Order By: Relevance
“…Particularly, the greatest increasing trends in annual rainfall at Hien station are estimated by 26.9%-31.3% for the 2080s under the worst-case scenarios (HadCM3 A2 and CanESM2 RCP8.5). It is worth noting that several previous studies [33,34] indicated increasing trends in annual rainfall over the VGTB river basin by applying bias correction approaches, which differs from those found in the present study. To a certain extent, these findings reflect various uncertainties in future projections of daily rainfall.…”
Section: Future Climate Projectionscontrasting
confidence: 99%
See 1 more Smart Citation
“…Particularly, the greatest increasing trends in annual rainfall at Hien station are estimated by 26.9%-31.3% for the 2080s under the worst-case scenarios (HadCM3 A2 and CanESM2 RCP8.5). It is worth noting that several previous studies [33,34] indicated increasing trends in annual rainfall over the VGTB river basin by applying bias correction approaches, which differs from those found in the present study. To a certain extent, these findings reflect various uncertainties in future projections of daily rainfall.…”
Section: Future Climate Projectionscontrasting
confidence: 99%
“…It is discernible that most previous investigations employed dynamical downscaling approach by applying Conformal Cubic Atmospheric Model (CCAM), Regional Climate Model Version 3 (RegCM3), Regional Model (REMO), and PRECIS models. In the Vu Gia Thu Bon (VGTB) river basin, Thanh and Dutto [33], Nam et al [34] employed a number of bias correction techniques to reduce systematic biases from the outputs of multiple GCMs/RCMs, which were subsequently used to assess the impacts of climate change on extreme flood events.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change, along with urbanization, causes severe impacts in Vietnam, like the intensification and durations of floods and droughts. These heat-related changes put ecosystems under stress and affect the wellbeing of the local population with extreme heat events [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Nhóm nghiên cứu đã báo cáo rằng phương pháp tính toán tần suất lũ thiết kế dựa trên đường cong IDF mưa là phù hợp và triển vọng áp dụng cho những khu vực khác của Việt Nam. Gây đây, năm 2018 [14] đã tiến hành một nghiên cứu xây dựng đường cong IDF mưa cho khu vực sông Vu Gia-Thu Bồn trong bối cảnh BĐKH, dựa trên chuỗi dữ liệu mưa ngày. Để tiến hành nghiên cứu này, nhóm tác giả đã sử dụng dữ liệu mưa lịch sử từ mô hình RegCM4 theo kịch bản RCP4.5 và RCP8.5 với độ phân giải lưới 10km x 10km.…”
Section: Mở đầUunclassified